Robust Th1 cellular and humoral responses generated by the Yersinia pestis rF1-V subunit vaccine formulated to contain an agonist of the CD137 pathway do not translate into increased protection against pneumonic plague. Issue 38 (10th September 2019) - Bowen, William; Batra, Lalit; Pulsifer, Amanda R.; Yolcu, Esma S.; Lawrenz, Matthew B.; Shirwan, Haval
Highlights: Sex bias observed for mice vaccinated with rF1-V subunit plague vaccine. Sex bias appears independent of antigen-specific antibody or cellular responses. SA-4-1BBL addition to vaccine formulation increases Th1 cellular responses. Boosting with the rF1-V vaccine with SA-4-1BBL protects against pneumonic plague. Balanced cellular/humoral response alone may not predict plague vaccine efficacy. Abstract: Yersinia pestis is the causative agent of plague and is a re-emerging pathogen that also has the potential as a biological weapon, necessitating the development of a preventive vaccine. Despite intense efforts for the last several decades, there is currently not a vaccine approved by the FDA. The rF1-V vaccine adjuvanted with Alhydrogel is a lead candidate subunit vaccine for plague and generates a strong Th2-mediate humoral response with a modest Th1 cellular response. As immune protection against Y. pestis requires both humoral and Th1 cellular responses, modifying the rF1-V subunit vaccine formulation to include a robust inducer of Th1 responses may improve efficacy. Thus, we reformulated the subunit vaccine to include SA-4-1BBL, an agonist of the CD137 costimulatory pathway and a potent inducer of Th1 response, and assessed its protective efficacy against pneumonic plague. We herein show for the first time a sex bias in the prophylactic efficacy of the Alhydrogel adjuvanted rF1-V vaccine, with female mice showing better protection against pneumonic plague than male. The sex bias for protection was irrespective of the generation of comparable levels of rF1-V-specific antibody titers and Th1 cellular responses in both sexes. The subunit vaccine reformulated with SA-4-1BBL generated robust Th1 cellular and humoral responses. A prime-boost vaccination scheme involving prime with rF1-V + Alhydrogel and boost with the rF1-V + SA-4-1BBL provided protection in male mice against pneumonic plague. In marked contrast, prime and boost with rF1-V reformulated with both adjuvants resulted in the loss of protection against pneumonic plague, despite generating high levels of humoral and Th1 cellular responses. While unexpected, these findings demonstrate the complexity of immune mechanisms required for protection. Elucidating mechanisms responsible for these differences in protection will help to guide the development of better prophylactic subunit vaccines effective against pneumonic plague.